Respostas

2014-03-13T17:13:21-03:00
O termo geral de uma PG é: an = a1.q^(n-1), onde, a1 é o primeiro termo, q é a razão da PG e n é o número de termos. Se a1 = a² e a2 = a⁵, a razão será:

an = a1.q^(n-1) => q^(n-1) = a2/a1 => q^(2-1) = a⁵/a² => q = a³, então:

a₃ = a² . (a³)² = a² .a⁶ = a⁸
a₄ =  a² . (a³)³ = a² .a⁹ = a¹¹
a₅ =  a² . (a³)⁴ = a² .a¹² = a¹⁴
a₆ =  a² . (a³)⁵ = a² .a¹⁵ = a¹⁷
a₇ =  a² . (a³)⁶ = a² .a¹⁸ = a²⁰
a₈ =  a² . (a³)⁷ = a² .a²¹ = a²³
a₉ =  a² . (a³)⁸ = a² .a²⁴ = a²⁶
a₁₀ =  a² . (a³)⁹ = a² .a²⁷ = a²⁹

PG (a², a⁵, a⁸, a¹¹, a¹⁴, a¹⁷, a²⁰, a²³, a²⁶, a²⁹)